2000
DOI: 10.1002/(sici)1520-6432(200005)83:5<21::aid-ecjb3>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

A study on UV-curable adhesive sealant for LCD panel

Abstract: With a view to suppressing the overlap shift between the TFT substrate and the color filter substrate, application of UV sealant is considered in the LCD panel assembly process. The initial tensile strength and moisture resistance of the UV sealant are evaluated and studied. In regard to the initial tensile strength, the stress applied to the sealing part during the glass cutting process, in which the peeling of the seal is most likely, is quantized by a numerical method based on the finite element method. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…LOCA is liquid at room temperature and has fluidity. Process flow of LOCA lamination can be divided into 4 steps of dispensing, lamination, leveling, and curing, 94 as shown in Figure 9. The main performance comparison between OCA and LOCA is given in Table 6.…”
Section: The Lamination Process Of the Touch Screenmentioning
confidence: 99%
“…LOCA is liquid at room temperature and has fluidity. Process flow of LOCA lamination can be divided into 4 steps of dispensing, lamination, leveling, and curing, 94 as shown in Figure 9. The main performance comparison between OCA and LOCA is given in Table 6.…”
Section: The Lamination Process Of the Touch Screenmentioning
confidence: 99%
“…Alternative methods such as UV and microwave assisted curing have been developed to solve these problems. UV curing has several advantages such as a solvent‐free process, low energy consumption, room temperature operation and shortened curing time; yet, severe curing shrinkage, low moisture resistance and insufficient strength are found in UV‐cured epoxy materials. It would be desirable to combine the advantages of UV‐ and thermo‐cure processes for protective coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet (UV)-curable sealant are widely applied to the surface protection of glass and to electronic components because this type of environment-friendly sealant exhibits numerous advantages such as high curing rate, little shrinkage and good chemical stability in room-temperature curing process [1][2]. For an example, Morii et al extended the UV-curable sealant to liquid crystal display (LCD) panels and their results showed that the UV curable sealant could be applied to the fabrication of LCD panels due to high tensile strength, low shrinkage, and good resistance to humidity [3]. However, the details on the synthesis of the UV-curable sealant have never been available for publicity because all the critical parameters were either patented or archived as secrets for high-tech companies.…”
Section: Introductionmentioning
confidence: 99%